2023
DOI: 10.3892/or.2023.8517
|View full text |Cite
|
Sign up to set email alerts
|

High expression of LY6E is an independent prognostic factor of colorectal cancer patients

Abstract: Colorectal cancer (CRC) is common cancer worldwide, and the 5-year relative survival rate of CRC patients with distant metastasis is as low as 14%. Therefore, identifying markers of CRC is important for the early detection of CRC and applying appropriate treatment strategies. The lymphocyte antigen 6 family (LY6 family) is closely related to the behavior of various cancer types. Among the LY6 family, the lymphocyte antigen 6 complex, locus E (LY6E), which is specifically highly expressed in CRC. Hence, the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…6 ). The present findings are consistent with the conclusions of Julio et al ( 20 ), which revealed that high ERK1/2 and p38 MAPK activity coexist in promoting the proliferative activity of melanoma M24MET cells ( 32 , 33 ), due to several isoforms of p38MAPK, α, γ and δ ( 24 ). By contrast, SNAI2 could trans-suppress the expression of Akt1/p-Akt1 by binding to E-box motifs in the promoter of the Akt1 gene and then inhibit the cell proliferation and tumor formation, not promote dormancy of cervical cancer cells, by upregulating p21/p27 and/or downregulating the activity of the Wnt/β-catenin signaling pathway ( 24 ).…”
Section: Discussionsupporting
confidence: 93%
“…6 ). The present findings are consistent with the conclusions of Julio et al ( 20 ), which revealed that high ERK1/2 and p38 MAPK activity coexist in promoting the proliferative activity of melanoma M24MET cells ( 32 , 33 ), due to several isoforms of p38MAPK, α, γ and δ ( 24 ). By contrast, SNAI2 could trans-suppress the expression of Akt1/p-Akt1 by binding to E-box motifs in the promoter of the Akt1 gene and then inhibit the cell proliferation and tumor formation, not promote dormancy of cervical cancer cells, by upregulating p21/p27 and/or downregulating the activity of the Wnt/β-catenin signaling pathway ( 24 ).…”
Section: Discussionsupporting
confidence: 93%
“…The LY6 family genes were found to be located on chromosome 8q24.3, in which human cancer genes are frequently amplified, and researches have pointed out that some LY6 family members play key roles in various tumors [45,46]. LY6A is aberrant expressed in pituitary tumors and can be a tumor-initiating biomarker of lung cancer [47,48]; LY6E can serve as an independent prognostic factor for CC and is closely associated with the migration and invasion of CC [23,24]; and LY6K promotes the progression of bladder, ovarian, and breast cancers [25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…High expression of LY6 family members is reportedly associated with poor prognosis of some cancers. High expression of LY6E enhances the progression of CC [23,24]. High expression of LY6K promotes the progression of bladder, ovarian, and breast cancer [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%